Adaptation and Validation of the Indonesian Version of R.I.G.H.T. Leadership Scale - Muksidah Pratiwi; Zahrotur Rusyda Hinduan; Fitriani Yustikasari Lubis; Cherrly April (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
Leadership has a significant impact on organizational resilience and employee well-being. In accordance with International Test Commission guidelines, this study translated and validated the R.I.G.H.T. Leadership Scale for Indonesian employees. Online information was gathered from 302 workers from various industries (162 men and 140 women, ages 19–41). Psychometric testing, expert review, and forward-backward translation were all part of the adaptation. With over 90% expert agreement, the content validity was excellent (I-CVI and S-CVI = 0.99). A good model fit was found by confirmatory factor analysis (χ² = 136.65, df = 80, p <.001; RMSEA = 0.036; CFI = 1.00; GFI = 0.94). With slight declines ascribed to cultural and linguistic factors, reliability was high (α = 0.804–0.884). Despite its limitations, which include young samples and a lack of test-retest data, the Indonesian version is generally valid, dependable, and helpful for evaluating leadership practices.